MODELING OF GOLD SORPTION ON CARBONACEOUS MATTER AT 20-500°C AND 1 KBAR - Plyusnina L.P.; Kuz'mina T.V.; Avchenko O.V. (My University, 2004)
The chemisorption of Au on carbonaceous matter (CM) was studied at 20-500°C and 1 kbar in water and in 1 m NaCl with application to the formation of gold mineralization in carbon-bearing complexes. The Au concentration was measured in the soluble organic fraction (SF), insoluble residue fraction (IF), and quench solution by atomic absorption spectrometry. The character of variations in the sorption capacity of CM in SF and IF with respect to Au is compatible with the existence of various types of organometallic compounds. The IR spectra of SF and IF suggest that CM underwent condensation and aromatization with increasing temperature. This process was accompanied by an increase in Au concentration in IF and insignificant changes in the sorption capacity of SF within a temperature range of 200-500°C. Aromatic compounds were prevailing at temperatures higher than 300°C and formed very strong bonds with Au. Aliphatic groups completely disappeared in SF and IF at 500°C, and amorphous carbon was graphitized preserving its high sorption activity with respect to gold. Thermodynamic calculations of equilibrium mass balance in the water-CM (or 1 m NaCl-CM) system in the presence of pyrite-pyrrhotitemagnetite (or hematite-magnetite) assemblages for the 250, 350, and 500°C isotherms (Ptot = 1 kbar) confirmed that CM is a potential-controlling (fo2 and pH) component in this system. The influence of chlorine and sulfur on gold sorption on carbonaceous matter is discussed.